CLASSIFICATION OF INTERACTIVE GENRES AND THEIR USAGE FEATURES IN INTERNET DISCOURSE - Vokhidova, Tamanno (QO‘QON UNIVERSITETI XABARNOMASI, 2024)
The study of interactive genres and their usage features in internet discourse is crucial to understanding the evolving landscape of digital communication. As online platforms continue to grow and diversify, so do the modes of interaction between users. This research aims to classify the various interactive genres in internet discourse and examine their distinctive features. Interactive genres are categorized based on their purpose, structure, and level of user engagement. We identify and analyze common genres such as social media posts, blogs, forums, comments, and live chats, exploring how each reflects the dynamics of virtual communication. The study also investigates the role of these genres in fostering interaction, shaping user identities, and influencing the flow of information. By examining both linguistic and non-linguistic features, including multi-modal communication, the paper provides a comprehensive understanding of how internet discourse facilitates new forms of social interaction. The findings offer insights into the complexities of online communication, highlighting the ways in which interactive genres contribute to the development of digital social practices.